Antibiotic Therapy for Crohn’s Disease: A Review - Simon Lal; A Hillary Steinhart (Canadian Journal of Gastroenterology)
Increasing evidence suggests that gut bacteria play a pathogenic role in Crohn’s disease (CD), providing a rationale for the use of antibiotics in the primary treatment of the disease. While there are data to suggest that antibiotics may be effective in treating active luminal, particularly colonic, and/or perianal CD, evidence for their use in these settings is hampered by the lack of well-designed, adequately powered, placebo-controlled trials. Furthermore, although nitroimidazole antibiotics have been shown to reduce postoperative recurrence following ileocolonic resection, their use is limited by side effects. There is a current need for rigorous multicentre studies looking into the role of antibiotics in treating perianal and luminal CD, as well as a need for the large-scale assessment of novel antibiotics, with low systemic absorption, which may improve patient tolerance.